Karakteristik dan Analisis Drug Related Problems (DRPs) Pasien Penderita Tuberkulosis Di Puskesmas Temindung Samarinda Kalimantan Timur - Nurul Fauziah; Islamudin Ahmad; Arsyik Ibrahim (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2014)
A study concerning the characteristics and Analysis of Drug Related Problems (DRPs) Patients with Tuberculosis Patients in Public Health Center (PHC) Temindung, Samarinda in East Kalimantan. The study was conducted using a prospective approach to the study of data sources in the form of primary data and secondary data. The primary data source is data from interviews with patients and through the provision of questionnaires and secondary data in this research is a Tuberculosis patient medical record data. Data collection was performed by analyzing the accuracy of the DRPs categories of accuracy of drugs, side effects and patient non-compliance. As well as the data recorded in the form of research support patient characteristics are age, sex, and education. Data were analyzed descriptively. Data obtained from patients with male gender 63.6% and women 36.4. Patient with age <15 years 4.5%, aged between 15-50 years and 68.2% aged> 50 years 27.3% . Based on the patient's level of education, no school 9.1%, graduated from elementary school22.7%, graduated from high school18.2%, graduated from high school40.1%, scholar 9.1%. Incidence of DRPs on drugs interactions 507%. Tuberculosis patient compliance rate of 81.8% in PHC Temindung adherent patients and 18.2% of patients do not comply Keywords: Tuberculosis, Drug Related Problems (DRPs) drugs interactions and patient compliance ABSTRAK Telah dilakukan penelitian tentang Karakteristik dan Analisis Drug Related Problems(DRPs) Pasien Penderita Tuberkulosis di Puskesmas Temindung, Samarinda Kalimantan Timur. Penelitian ini dilakukan dengan menggunakan pendekatan prospektif dengan sumber data penelitian berupa data primer dan data sekunder. Sumber data primer adalah data hasil wawancara dengan pasien dan melalui pemberian kuisioner sedangkan data sekunder dalam penelitian ini adalah data rekam medik pasien Tuberkulosis. Pengumpulan data dilakukan dengan menganalisis DRPs kategori interaksi obat dan ketidakpatuhan pasien. Serta dicatat data pendukung penelitian berupa karakteristik pasien yaitu usia, jenis kelamin, dan tingkat pendidikan.Data dianalisis secara deskriptif.Dari data yang diperoleh pasien dengan jenis kelamin laki-laki 63,6% danperempuan 36,4%.Pasien yang berusia < 15 tahun 4,5%, usia antara 15-50 tahun 68,2% dan usia > 50 tahun 27,3%. Berdasarkan tingkat pendidikan pasien, tidak sekolah 9,1%,lulus SD 22,7%,lulus SMP 18,2%,lulus SMA 40,1%, sarjana 9,1%. Kejadian DRPs mengenai interaksi obat 50%.Tingkat kepatuhan pasien Tuberkulosis di Puskesmas Temindung 81,8% pasien patuh dan 18,2% pasien tidak patuh. Kata kunci: Tuberkulosis, Drug Related Problems (DRPs), Interaksi Obat, Kepatuhan pasien.